SCANNING ELECTRON MICROSCOPIC EVALUATION OF THE SEALER/DENTINE INTERFACE OF TWO SEALERS USING TWO PROTOCOLS OF IRRIGATION - Elvira Gyulbenkiyan (Peytchinski Publishing, 2020)
Purpose: To evaluate with scanning electron microscopy the sealing ability of the bioceramic sealer Total Fill BC and the resin-based sealer AH Plus using two protocols of irrigation. Materials and Methods: All teeth (n = 40) were prepared using a crown-down technique with rotary nickel-titanium instruments. Two irrigation protocols are used for the purpose of this in vitro study: first (classical) protocol - 10 ml 2.0% NaOCl, 10 ml 17% EDTA and 10 ml saline, and second (modified) protocol - 10 ml 2.0% NaOCl, 3 ml 0.6% chitosan-citrate and 10 ml saline. All teeth were allocated into four groups: group I (n = 10) - the first (classical) irrigation, obturation with AH Plus; group II (n = 10) - the second (modified) irrigation protocol, obturation with AH Plus; group III (n = 10) - the first (classical) irrigation protocol, obturation with Total Fill and group IV (n = 10) - the second (modified) irrigation protocol, obturation with Total Fill BC. The adaptation of the sealer in the sealer/dentin interface (using SEM) was analyzed as the gap between the sealer and the dentine wall in 2 mm from the apex of the tooth was measured in microns. Results: There was a statistically significant difference between groups with the different protocol of irrigation. Conclusion: It was found that the application of chitosan-citrate 0.6% as final irrigating solution contributes high sealing ability both of the premixed bioceramic sealer Total Fill BC and the epoxy resin-based sealer AH Plus.